Bridging Tradition and Multiculturalism in Islamic Jurisprudence Education - Sayyi, Ach.; Asmuki, Asmuki; Juandi, Wawan; Alimin, Miftahul; Fithriyah, Imaniyatul (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
The purpose of this study is to explore the development of fiqh education at Ma'had Aly Situbondo, an Islamic boarding school that integrates a multi-madhhab approach with democratic pedagogy and multicultural education. This study aims to identify how the multi-madhhab curriculum and democratic learning methods improve students' fiqh competence and intercultural skills. This approach focuses on more inclusive and adaptive learning, in line with the needs of contemporary multicultural societies. The methodology used is a mixed methods approach, combining qualitative and quantitative techniques. The main data sources are curriculum documentation, interviews with educators, administrators, and students, as well as participatory observation at Ma'had Aly Situbondo. The research population involves Ma'had Aly Situbondo students with a purposively selected sample. Qualitative data analysis techniques used thematic analysis, while quantitative data were analysed using descriptive statistics and paired sample t-tests to measure changes in student competence before and after participating in the multi-madhhab curriculum programme. The findings show a significant increase in fiqh understanding, fiqh application skills, and student confidence in making decisions based on a multi-madhhab perspective.